Profil Pointing dan Representational Gesture Siswa dalam Menyelesaikan Soal Matematika Materi Fungsi Linear - Ewan Gunawan; Erry Hidayanto; Rustanto Rahardi (Graduate School of Universitas Negeri Malang, 2021)
Abstract: This study used a qualitative-descriptive study with the aim of this study to describe the pointing profile and gesture representation of students in solving mathematical problems with the material of linear functions. The subjects in the study were 2 students of class X SMA Negeri 2 Dompu. The research subjects were selected by 1 student as the pointing gesture and 1 student as the representational gesture. Data was collected by providing assignments, gesture observation sheets, and interviews with selected subjects. The data were analyzed qualitatively through data reduction, data presentation, and drawing conclusions. This study resulted that the pointing gesture helped P1 describe the answer completion plan, helped focus himself to perform calculations, generate ideas, and facilitate the description of information from questions and answers as well as check and understand questions and answers when solving questions. Representational gesture helps R1 to describe the steps to understand the graphic related to the problem, helps focus on understanding the problem and can be careful in solving the problem. Also plays a role in concretizing ideas/ideas that are being worked on or are being thought of by students.Abstrak: Penelitian ini menggunakan penelitian kualitatif-deskriptif dengan tujuan penelitian ini untuk mendeskripsikan profil pointing dan representasi gesture siswa dalam menyelesaikan soal matematika materi fungsi linear. subjek dalam penelitian adalah 2 orang siswa kelas X SMA Negeri 2 Dompu. Subjek penelitian dipilih 1 orang siswa sebagai pointing gesture dan 1 orang siswa sebagai representational gesture. Perolehan data dilakukan dengan memberikan lembar tugas, lembar Observasi gesture, dan wawancara yang terpilih menjadi subjek. Data di analisis secara kualitatif melalui reduksi data, penyajian data, dan menarik kesimpulan. Penelitian ini menghasilkan bahwa Pointing gesture membantu P1 menggambarkan rencana penyelesaian jawaban, membantu memfokuskan dirinya untuk melakukan hitungan, memunculkan ide, dan mempermudah gambaran informasi dari soal dan jawaban serta mengecek dan memahami soal dan jawaban saat menyelesaikan soal. Representational gesture membantu R1 untuk menggambarkan langkah memahami grafik terkait hubungan dengan soal, membantu memusatkan perhatian memahami soal dan dapat teliti dalam menyelesaikan soal. Berperan juga untuk mengkongkretkan ide/gagasan yang sedang dikerjakan maupun sedang dipikirkan siswa.